Os ideais de civilização na Amazônia imperial: um estudo sobre os projetos de civilização indígena no Pará (1845-1889) - SOUSA, Eveline Almeida de (Universidade Federal do Pará, 2014)
This paper examines the projects of indigenous civilization developed by four intellectuals of the Second Empire who lived in the province of Para in this period. Their names are: Henrique de Beaurepaire Rohan, Couto Vieira de Magalhães, Antonio Macedo Costa and José Verissimo. Their perceptions about the indigenous civilization are considered, by one side, as considering the specifics of the intellectual condition of the Empire, emphasizing the provision of such scholars within the field with the intellectual and their connections within the power field; on the other side, they are considered under the social lens of these agents, regarding to their ideological beliefs, their work, the debates and political struggles in which they were involved, these elements were active in their political action and in the formulation of their ideas. Such notions are consistent with the experience built in amazon space, which contributed to the preparation of their visions about indigenous civilization. Thus, perceptions about the Indigenous people were related with political and intellectual attitudes of the intellectual agents of the Empire , as it was with their experience in the amazon valley.